Analisis Ketimpangan Penguasaan dan Pemilikan Tanah Pasca Reforma Agraria di Indonesia - Umar, Mahmud Hi.; Suwarti; Papuluwa, Nurlaila Kadarwati (Syntax Corporation, 2023)
Reforming agrarian law will only be successful if agrarian law prioritizes farmers as the main pillar of national economic development, without ignoring the interests of investors and large investors as a source of development financing. In following up on the policy of reforming Agrarian law as regulated in the UUPA, the government has issued a decree as outlined in MPR Decree Number: IX/MPR/2001 concerning Agrarian Reform and Natural Resource Management. To overcome problems that will later hinder the implementation of agrarian law reform in Indonesia, Pancasila and the 1945 Constitution must be used as the ideal basis and constitutional basis for every legal act carried out by the State, meaning that regulations or policies issued in the context of implementing agrarian law reform must be based on on Pancasila and the 1945 Constitution. Agrarian conflict is still a legal problem in Indonesia. The presence of a strategy in the form of agrarian reform is expected to be able to make a real contribution in realizing social justice and people's prosperity for all Indonesian people. The implementation of agrarian reform is characterized by comprehensive asset management and access management, so it is important to carry out a comprehensive evaluation with fairness and community empowerment. The results obtained from this research show that the organizers of agrarian reform are expected to be able to guarantee increased community welfare and realize social justice, whether through the efforts of the Agrarian Reform Task Force (GTRA) or the Government which carries out a compromise strategy with ministries/institutions to ensure land rights through agrarian reform.